Entrepreneurial agility and organizational performance of IT firms: A mediated moderation model - Leul Girma Haylemariam; Stephen Oduro; Zewdu Lake Tegegne (Journal of Entrepreneurship, Management and Innovation, 2024)
PURPOSE: The Information and Communication Technology (ICT) sector is playing an important role in the growth of the world`s economy. However, limited knowledge exists concerning the underlying mechanisms and boundary-spanning conditions under which entrepreneurial agility (EA) affects the organizational performance (OP) of IT firms. This study draws on the Dynamic Capability Theory (DCT) to examine the effect of entrepreneurial agility (EA) on the organizational performance (OP) of Italian IT firms with the mediating role of open innovation (OI) and the moderating role of environmental dynamism (ED). METHODOLOGY: Employing an explanatory research design and convenience sampling technique via an online survey to gather data from a sample of 411 Italian IT firms, the study tested the formulated hypotheses using the structural equation modeling technique in AMOS statistical software. FINDINGS: The results revealed that EA, directly and indirectly, influences OP of IT firms. Moreover, the mediation analysis unveils that OI plays a complementary, partial mediation role in the EA—OP nexus. Finally, ED moderates this focal relationship, such that in the presence of high environmental dynamism, the relationship between EA and OP gets stronger compared to low environmental dynamism. IMPLICATIONS: The findings imply that IT firms should emphasize adopting agile procedures and structures that allow them to react to new problems and opportunities swiftly by building a culture of innovation through the adoption of OI strategies (inbound, outbound, and coupled) to tap into the broader range of expertise and resources in the business environment. To improve the link between OI and OP, managers should prioritize building relationships with external partners, such as customers, suppliers, and academic institutions. IT firms should also prioritize building a diverse and inclusive workforce that can bring diverse perspectives and experiences to the innovation process to enhance their innovation capabilities and create products and services that better meet the needs of customers. ORIGINALITY AND VALUE: The study´s value lies in extending the ongoing scholarly discussion on the nexus between EA and OP by exploring OI as an intermediary mechanism that connects EA, OP, and ED as a boundary-spanning condition that moderates the focal relationship. This research highlights the interplay between EA, OI, ED, and OP, using the DCT as a theoretical foundation. It is the first to examine such interrelationships in the IT sector. In addition, the study provides new insight for researchers focusing on the information technology (IT) sector.